Konflik Peran Ganda Perempuan Terhadap Kinerja Melalui Stress Kerja Pada Karyawan Bank - Boge Triatmanto; Nanik Wahyuni (IQTISHODUNA, 2023)
This study aims to investigate the effect of multiple role conflict on employee performance through work stress. This study uses a quantitative causality approach to determine the relationship between variables. The population of this study were 73 bank employees. The sampling technique uses the simple random sampling method to ensure that all populations have the same opportunity to be selected as research objects. The data source used is primary data in the form of a questionnaire. Data were analyzed using path analysis and using SPSS as an analytical tool. The results of this study indicate that multiple role conflict has a negative and significant effect on employee performance. Multiple role conflict has a positive and significant effect on work stress. Work stress has a negative and significant effect on employee performance. The results of the mediation analysis found that work stress is able to mediate the effect of multiple role conflict on employee performance.